Find G. y" - 4y' + 3y = 3x^2 - 2x - 3. H. y" - 4y' + 3y = 9x^2 I. y' - 4y = 2e^2x J. y' -4y =...



G. {eq}y" - 4y' + 3y = 3x^2 - 2x - 3{/eq}

H. {eq}y" - 4y' + 3y = 9x^2{/eq}

I. {eq}y' - 4y = 2e^{2x}{/eq}

J.{eq}y' -4y = 2e^{3x}{/eq}

Q. {eq}y'- 4y = (- 8x^2 + 2x - 4)e^x{/eq}

R. {eq}y' - 4y = x^2e^x{/eq}

S. {eq}y' - 4y =(- 8x - 4)e^{4x}{/eq}

Non-Homogeneous Second Order Differential Equation:

To solve a non-homogeneous linear differential equation of second order with constant coefficients,

{eq}a\frac {\partial^2 y}{\partial x^2} +b\frac {\partial y}{\partial x} +cy =g(x)\\ a \,\,\, b \,\,\, c \,\,\,\, \textrm {constants}\\ {/eq}

we must look for the complementary solution {eq}y_c {/eq} and find the particular solution {eq}y_p {/eq} of the non-homogeneous equation.

Then, the general solution is: {eq}y = y_c + y_p {/eq}

One of the methods to find the particular solution is that of undetermined coefficients. This method is used when g (x) has a special form, involving only polynomials, exponentials, sines and cosines, or g (x) is a finite linear combination of this functions.

The method is called the undetermined coefficients method because it is a coherent proposal about the form of the particular solution.

Answer and Explanation: 1

Become a member to unlock this answer!

View this answer

Find G. {eq}\displaystyle y" - 4y' + 3y = 3x^2 - 2x - 3 {/eq}

Step 1. Calculate the solution of the associated homogeneous equation


See full answer below.

Learn more about this topic:

Separable Differential Equation: Definition & Examples


Chapter 16 / Lesson 1

Discover what separable differential equations are and their uses. Learn to identify if an equation is separable and how to solve them through given examples.

Related to this Question

Explore our homework questions and answers library